Addictive Facebook use among university students - Zaremohzzabieh, Zeinab; Abu Samah, Bahaman; Omar, Siti Zobidah; Bolong, Jusang; Kamarudin, Nurul Akhtar (Canadian Center of Science and Education, 2014)
The Facebook has become an essential part of almost every university students’ daily life, and while a large number of students seem to get benefits from use of the Facebook by exchanging information for educational goals, make friends, and other activities, the literature indicates that this social networking site can become addictive to some university students’ users, which is one of the today’s higher education matters. The aim of this study, therefore, is to explore the phenomenon of Facebook addiction among university students. Qualitative study using interview is used to gather data from nine International postgraduates of Universiti Putra Malaysia and the data established three themes (Compulsion to check Facebook, High frequency use, and Using Facebook to avoid offline responsibility) relied on the participants interviews. The findings from these three themes showed that these users considered their Facebook dependency, are known as salience, tolerance, and conflict. These results also lead to the conclusion that like most activities, moderation and controlled use are key. So, the best approach to preparing students for life in a knowledge-based society is to help them exercise self-control and achieve a level of balance when using Facebook. It is believed that the findings of this study would help other Facebook researchers by contributing to the limited academic literature in this area.